Perbaikan dan Evaluasi Penerapan Sistem Manajemen Mutu pada Industri Pengolahan Tahu (Studi Kasus di UD Cinta Sari, DIY) - Sapta Raharja; S. Joni Munarso; Dian Puspitasari (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2012)
Regarded as a tool for improving quality and potentially other performance related outcomes, quality management system (QMS) ISO 9000:2000 and Hazard Analyzis Critical Control Point (HACCP) approach are held as a key way of achieving competitive advantages in the today’s global work context, especially for tofu industry. QMS is designed for use in all segments of the food industry from procurement and handling raw material, controlling operator competency, operasionalize of technology, process documentation. HACCP requires the development of strategies to prevent the inclusion or reduction of these hazard until acceptable level in a food. Research methodology empyoyed in these research comprises of 5 steps i.e: (1) Tofu manufacturing inventarization; (2) Composing of Manual of Quality dan Work Instruction are main prerequire for QMS implementation; (3) Implementation of Quality Escort which is part in QMS; (4) Comparison study before and after QMS Implementation; (5) Consistency observation quality product with statistical analysis dan quality control chart; include: moisture, ash, protein content, compactcity of tofu structure. The result  is quality of product more consistence after QMS Implementation. Neverless, it needed recontruction and monitoring contineously better way to create integrated agroindustry which is QMS implementation.